2021
DOI: 10.1016/j.ijscr.2021.105827
|View full text |Cite
|
Sign up to set email alerts
|

Case report of Brunner’s gland hyperplasia: A rare “mimic” of malignant pathology

Abstract: Highlights BGH is a rare, benign condition to consider in a patient with epigastric pain, dyspepsia, weight loss and upper gastrointestinal bleeding. The diagnosis involves multiple modalities including CT, MRI, endoscopic ultrasound and biopsies. It is important to determine the correct diagnosis to reduce the risk of overtreating a benign condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
1
4
0
Order By: Relevance
“…1 McCafferty et al, reported that most of the lesions are located at the first part of the duodenum (70%), with decreasing incidence distally. 2 The present study showing coherence with this study (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…1 McCafferty et al, reported that most of the lesions are located at the first part of the duodenum (70%), with decreasing incidence distally. 2 The present study showing coherence with this study (Table 1).…”
Section: Discussionsupporting
confidence: 87%
“…The underlying etiology of BGH is unknown. Numerous articles and studies have hypothesized that BGH results from excessive acid secretion, Helicobacter pylori infection, or inflammation encouraging the production of alkaline secretions by the Brunner's gland cells [1][2][3][4]. The reduced pancreatic exocrine function may also be the cause.…”
Section: Discussionmentioning
confidence: 99%
“…The reduced pancreatic exocrine function may also be the cause. However, it is now believed that the primary component causing BGH is the exocrine modifying factor, which includes the hormone, vagus nerve, and intestinal mucous membrane factor [ 3 , 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopically, it may present as a mucosal prolapse/ duodenal polyp (if >5mm is called brunner's gland hamartoma) or, rarely, an infiltrative duodenal mass (diffuse nodular hyperplasia). It is usually asymptomatic but, rarely, symptoms/complications like bleeding, obstruction and abdominal pain may arise (1,2). The main differential diagnoses are pancreatic or duodenal neoplasms and groove pancreatitis (3).…”
Section: What Is the Diagnosis?mentioning
confidence: 99%